الإدغام بين الخفة والثقل أسسه، والعوامل المؤثرة فيه - عوض, سامي; منصور, رائد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
الإدغام في اللغة العربية ظاهرة صوتية سياقية، يلجأ إليها الناطق طلباً للخفة واختصاراً للجهد العضلي، وقد وقف الدرس اللغوي العربي عند الإدغام وقسمه بحسب نوع الأصوات إلى قسمين: الأول: إدغام المتماثلين (التضعيف): ويتعلق بالعملية النطقية للصوت، فعند نطق الصوت المكرر يثقل على المتكلم أن يعيد العملية النطقية نفسها، فلا يجيء بها إلا مرة واحدة عن طريق الإدغام، وفي ذلك خفة وسهولة واختصار للجهد وسرعة في النطق. الثاني: إدغام المتقاربين: وفيه نقف على أصوات متجاورة يتأثر بعضها ببعض عند النطق بها فتتغير مخارج الأصوات أو صفاتها لكي تتفق في المخرج أو الصفة مع الأصوات المجاورة لها عن طريق فناء الصوت الضعيف (المتأثر) في الصوت القوي (المؤثر) فنحصل على نوع من المماثلة أو المشابهة بين تلك الأصوات، ويزداد مع مجاورتها قربها في الصفات أو المخارج وصولاً للانسجام الصوتي بينها وفي ذلك خفة واختصار للجهد العضلي المبذول. وقد نجح الدرس اللغوي العربي القديم في فهم حقيقة الإدغام، حين اعتبره نوعاً من التقريب بين الأصوات، وظاهرة سياقية تنتج عن استعمال مجموعة صوتية متجاورة لها صفاتها الخاصة ونظامها الخاص، ووضع له الأسس والقواعد المناسبة وبيّن العوامل المؤثرة فيه. Assimilation (Idġam) in Arabic is an environmental phonological phenomenon which the speaker resorts to seeking lightness or smoothness; thus minimizing muscular effort. Ancient Arabic linguistics studied assimilation and divided it into two kinds based on contracted sounds: The first kind is gemination (tađ’eef) (assimilation of two identical sounds), which means the contraction of two similar letters or sounds into one. It is connected with the articulation of sounds. Upon articulating the doubled sound, it is difficult for the speaker to repeat the same process once again. Through gemination (idġam) the speaker performs the process only once. It results in lightness, easiness, swiftness of articulation and reduction of the muscular effort required. The second kind: Assimilation, which means the incorporation of two close sounds. Adjacent phonemes influence one another when uttered, so that their places of articulation and characteristics change to correspond in articulation and characteristics with adjacent sounds. The weaker (affected) sound is contracted into the stronger (affecter) sound, so a kind of assimilation or similitude of sounds occurs. The closer the sounds in characters or nearer in places of articulation are the more the assimilation occurs, in the end coming to phonological harmony. This is much lighter and it reduces muscular effort. Ancient Arabic linguistics succeeded in understanding assimilation considering it a kind of amalgamation of sounds and an environmental phenomenon resulting from using a group of adjacent sounds having its own characteristics and its own system. It also founded its bases and adequate rules and showed factors affecting it.